Pelaku Pembunuhan yang Membela Diri dalam Mempertahankan Kehormatan dan Harta - Marsudi Utoyo (PRANATA HUKUM, 2013)
Article 49 paragraph (1) of the Criminal Code regulates the actions "emergency defense" (noodweer) for themselves and for others, decency, honor or property themselves or others, because there is an attack or threat of attack is very close. According to this article people who do defense emergency can not be punished. Factors That Makes Working Out Perpetrators of Criminal Punishment by Penal Code are: Ontoerekenings-vatbaarheid (an inability responsible), Overmacht (necessity) forced or emergency, Noodweer (urgent advocacy), Wettelijk voorschrif (command laws), bevel Ambtelijk (command term)